2015
DOI: 10.5348/ijcri-201548-cr-10509
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of gallbladder: A diagnostic dilemma

Abstract: International Journal of Case Reports and Images (IJCRI) is an international, peer reviewed, monthly, open access, online journal, publishing high-quality, articles in all areas of basic medical sciences and clinical specialties.Aim of IJCRI is to encourage the publication of new information by providing a platform for reporting of unique, unusual and rare cases which enhance understanding of disease process, its diagnosis, management and clinico-pathologic correlations. Agenesis of gallbladder is a rare (13-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…A few experts recommend conversion to laparotomy during surgical procedure to facilitate an accurate investigation of heterotopic sites of gallbladder. 6 Other investigators proposed intraoperative cholangiograhy or invasive procedure of the bile duct 1 7 14 while others discourage these approaches due to possible complications and recommend further radiological investigation. 1 15 …”
Section: Discussionmentioning
confidence: 99%
“…A few experts recommend conversion to laparotomy during surgical procedure to facilitate an accurate investigation of heterotopic sites of gallbladder. 6 Other investigators proposed intraoperative cholangiograhy or invasive procedure of the bile duct 1 7 14 while others discourage these approaches due to possible complications and recommend further radiological investigation. 1 15 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that intraoperative ultrasound and postoperative MRCP or EUS can help in the diagnosis of agenesis or ectopic gallbladder. Overall, it is thought that ultrasonography is the primary imaging modality for gallbladder anomalies with CT, MRI being even more helpful, and the MRCP or EUS providing a more thorough visualization of the biliary tract [31,34,35].…”
Section: Eus and Gallbladder Anomaliesmentioning
confidence: 99%